Towards the elimination of viral hepatitis in Thailand by the year 2030 - Nawarat Posuwan; Nasamon Wanlapakorn; Palittiya Sintusek; Rujipat Wasitthankasem; Kittiyod Poovorawan; Sompong Vongpunsawad; Yong Poovorawan (Elsevier, 2020)
Viral hepatitis is a global problem with mortality comparable to HIV, tuberculosis and malaria. The WHO aims to eliminate hepatitis B (HBV) and hepatitis C (HCV) by 2030. Improved socioeconomic status of developing countries such as Thailand has reduced the incidence and morbidity associated with hepatitis A. Since the beginning of hepatitis B vaccination in all Thai newborns in 1992, at least 95% of one-year-olds are currently receiving 3-4 hepatitis B doses. The second vaccination of newborns of carrier mothers at 1 month of age has contributed to an effective reduction in mother-to-child transmission. Universal vaccination, blood donation screening, and decreasing needle sharing have reduced hepatitis B infection. Under the test and treat model, cost-effective screening at the point-of-care (health center or village hospital) is recommended for adults >30 years-old. Following referral to a tertiary healthcare center for a treatment plan in developing disease management plan, its implementation by trained healthcare professionals is preferably administered at the point-of-care. Hepatitis C prevalence is also decreasing as a result of blood-borne pathogen awareness. Current hepatitis C infection is highest for adults >35 years who were born prior to 1983, with screening is recommend once in their lifetime. Treatment strategy recommendation follows that of hepatitis B. The availability of direct antiviral agents with high cure rates is expected to contribute to the reduction in hepatitis C transmission and mortality as set forth by the WHO policy. Thus, ensuring the successful planning of hepatitis elimination in Thailand requires pilot regional assessment prior to national implementation.